Politically acceptable debt restructuring in the euro zone: Is it really better than the redemption fund? - Ester Faia (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
This article discusses the recent proposal for debt restructuring in the euro zone by Pierre Paris and Charles Wyplosz. It argues that the plan cannot realize the promised debt relief without producing moral hazard. Ester Faia revisits the Redemption Fund proposed in November 2011 by the German Council of Economic Experts and argues that this plan, up to date, still remains the most promising path towards succesful debt restructuring in Europe.
urn:nbn:de:hebis:30:3-336368
Keywords: 330; public debt; debt restructuring